Distribution and habitat assessment of an Endangered hummingbird: the Grey-bellied Comet Taphrolesbia griseiventris. (13th March 2023) - Cuadros, Sandra; Angulo, Fernando
Summary: The Grey-bellied Comet ( Taphrolesbia griseiventris ) is a hummingbird species endemic to northern Peru and listed as Endangered by IUCN due to its small and fragmented population. Despite this, little has been attempted to increase knowledge of its natural history and ecology to provide current information and better evaluate its conservation status. Here, we used known curated records of the species from the literature to generate a model of its potential distribution using MaxEnt, and we then validated the model in the field through direct observation in selected areas. Where the species was confirmed, we conducted a habitat characterisation with field data, and a threat assessment of the landscape using secondary data in ArcGIS. We found five new records of the species in the department of La Libertad at two different sites, confirming a new population. The habitat mostly comprised Andean scrub (17.6%) throughout its distribution, and the main threat in the habitat was human-induced fires for agricultural purposes and as a means of waste disposal. Our findings revealed new information on the distribution of the species with a potential habitat occupancy of 4–6% within its range. Furthermore, areas that were previously reported to harbour a population of the species no longer showed records despite intensive searches in the field. Finally, we discuss the implications for its conservation. Our results indicated that conservation measures to protect the Grey-bellied Comet are urgently needed, especially the declaration of a reserve in La Libertad, which might be the only area where the species is reliably present with good quality habitat.